Evaluasi Reliability VHF Ground To Air (A/G) Approach Control Service (APP) Di Bandara Sultan Syarief Kasim Pekanbaru - Dara Incam Ramadhan; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Very High Frequency (VHF) Gound to Air (A/G) Approach Control Service (APP) Radio device consists of a transmitter and a receiver. Each transmitter and receiver consists of main transmitter (primary) and backup (standby / secondary). VHF A / G that has a frequency limit of 118-137 MHz. The power emitted by the VHF-A / G antenna within the APP area is in the range of 30-50 Watts. The control of VHF-A / G communication performance is carried out in the APP area when the airplane is at altitudes ranging from 0-20000 ft outside the airport lane. In this case, the Transmitter and Receiver have a level of reliability that supports the equipment performance. Moreover, it is the MTBF and the condition of the equipment that act as reference in determining the increase of Reliability. Based on the data, it showed that the reliability of the MTBF from 2017-2018 remained constant, there was no significant change, which was 36.78%. The condition of the reliability VHF A/G APP primary in 2016 was 60% and secondary 100%, meanwhile in 2017 was 53% and 93%, and in 2018 was 46.67% and 86.67%. After obtaining the reliability value, it is adjusted to the readability (Readibility) of ATC and the pilot uses the Level Indicator method. Readibility produced in 2018-2019 from VHF APP primary obtained scale 4. In the meantime, due to the disturbance on the secondary scale that occurred at the end of 2018 and the beginning of 2019, the readability got scale 1.Keywords: Reliability, Readibility, MTBF, Condition , Level Indicator, VHF A/G